Relationship between sustainability reporting and firm value - Amin, Hod; Kadri, Mohd Halim; Raja Ahmad, Raja Adzrin (UiTM Cawangan Johor, 2024)
Firm value, commonly known as enterprise value or market value, is a vital indicator used to gauge a company's financial health and potential for long-term growth. The study examines the impact of sustainability reporting on the market value of firms. Utilising Stata for data analysis, this research focuses on firms listed on the Main Market of Bursa Malaysia. The population for the study includes 66 firms over a period of five years, resulting in a total of 330 firm-year observations. The findings reveal that firm value is significantly and positively related to sustainability reporting. Additionally, the study identifies a significant and positive relationship between firm value and the control variables, namely earnings, leverage and size of firm. These results suggest that sustainability reporting, alongside traditional financial metrics, provides essential information for investors and the market, contributing to the formation of market price and, consequently, firm value. Accordingly, the study highlights the importance of sustainability reports in financial decision-making processes and their role in enhancing transparency and providing a comprehensive view of a firm's performance. It offers valuable insights for investors, regulators, and corporate managers.